Design and optimization of offshore ship-based natural gas storage technologies in the South China Sea. (1st July 2021) - Fan, Shuanshi; Wang, Yan; Wang, Yanhong; Lang, Xuemei; Wang, Shenglong
Highlights: Ship-based gas storage processes were optimized for off-shore natural gas hydrate production. Energy, exergy, equipment weight, and economy were analyzed and compared. Hydrate-based technology is prominent in net present value calculation. Hydrate-based storage system is found applicable for small-scale gas storage of hydrate exploitation. Abstract: China's second offshore natural gas hydrate production reveals the urgency and potential demand for ship-based gas storage and transportation technology. Three possible gas storage processes including hydrate-based natural gas (HNG), pressurized liquefied natural gas (PLNG), and compressed natural gas (CNG) processes were simulated and optimized from aspects of specific energy consumption ( SPC ), exergy efficiency, equipment weight, and capital expenditure (CAPEX) respectively. The SPC of HNG, PLNG, and CNG was 0.22, 0.48, and 0.24 kW h kg −1 respectively. While the CAPEX of HNG, PLNG, and CNG for gas storage production was 363.3, 405.0, and 384.8 10 3 US Dollars respectively. And HNG showed a payback period of 1 year in the evaluation of natural gas value chain. The comparison results indicate that HNG has low SPC, CAPEX, equipment weight, and short payback period but high exergy efficiency among the three processes, which provides a promising offshore ship-based gas storage process to offshore small-scale natural gas production.